2007
DOI: 10.1183/09031936.00040007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of QuantiFERON TB-2G test for immunocompromised patients

Abstract: The usefulness of the tuberculin skin test (TST) and the QuantiFERON TB-2G (QFT-TB) test were compared in immunocompromised patients.The subjects consisted of 252 immunocompromised patients who were clinically suspected of tuberculosis (TB) infection between April 2005 and December 2006.Regarding the underlying diseases, 74 subjects had malignant diseases, 72 were undergoing immunosuppressive treatment, 52 had diabetes mellitus, 50 had chronic renal failure and four had HIV infection. While the positive rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
3
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 23 publications
(26 reference statements)
9
79
3
6
Order By: Relevance
“…However, making a diagnosis tends to be difficult and delayed since patients commonly present with extrapulmonary involvement and nonspecific symptoms mimicking uremia (6,7). To date, few research groups have applied QuantiFERON TB-2G (QFT-2G) (Cellestis Ltd., Carnegie, Victoria, Australia) a diagnostic test for tuberculosis using Mycobacterium tuberculosisspecific antigens, early secreted antigenic target , and culture filtrate protein for dialysis patients (8). Furthermore, a previous study reported a lack of health-care facilities for such patients in Japan (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, making a diagnosis tends to be difficult and delayed since patients commonly present with extrapulmonary involvement and nonspecific symptoms mimicking uremia (6,7). To date, few research groups have applied QuantiFERON TB-2G (QFT-2G) (Cellestis Ltd., Carnegie, Victoria, Australia) a diagnostic test for tuberculosis using Mycobacterium tuberculosisspecific antigens, early secreted antigenic target , and culture filtrate protein for dialysis patients (8). Furthermore, a previous study reported a lack of health-care facilities for such patients in Japan (9).…”
Section: Introductionmentioning
confidence: 99%
“…A tuberculin skin test, which is often used in the general population, is less useful in hemodialysis patients because impaired cellular immunity yields a high prevalence of false-negative results [3][4][5]. The principle behind IGRA is to quantitatively assess activation of monocytes by measuring the amount of interferon-gamma released from CD4-positive lymphocytes exposed to specific antigens that are related to Mycobacterium tuberculosis: early secreted antigen target 6 and culture filtrate protein 10 [14]. Importantly, IGRA does not respond to other mycobacterium species, even Bacille CalmetteGuerin, enabling the use of IGRA instead of the tuberculin skin test for patients previously vaccinated with Bacille Calmette-Guerin.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that 31% of patients with TB disease were QFT-G positive and TST negative, whereas none were QFT-G negative and TST positive. 8 In our study, there were four patients on immunosuppressive medications: two tested QFT-G positive, one negative, and one indeterminate. There were no patients with HIV infection or lymphopenic disorders.…”
Section: Discussionmentioning
confidence: 99%